2017
DOI: 10.1103/physrevlett.119.188002
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Ultrastability in Vapor-Deposited Glasses

Abstract: Glass films created by vapor-depositing molecules onto a substrate can exhibit properties similar to those of ordinary glasses aged for thousands of years. It is believed that enhanced surface mobility is the mechanism that allows vapor deposition to create such exceptional glasses, but it is unclear how this effect is related to the final state of the film. Here we use molecular dynamics simulations to model vapor deposition and an efficient Monte Carlo algorithm to determine the deposition rate needed to cre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…where the second term stems from the γ 2 term in yy , see Eq. (11). Noticing that V −1 ∂U/∂ yy −p, and following Eq.…”
Section: A Poisson's Ratiomentioning
confidence: 98%
See 1 more Smart Citation
“…where the second term stems from the γ 2 term in yy , see Eq. (11). Noticing that V −1 ∂U/∂ yy −p, and following Eq.…”
Section: A Poisson's Ratiomentioning
confidence: 98%
“…Mechanical annealing by means of oscillatory shear was also recently shown to be an efficient protocol for creating stable glasses [8]. Finally, numerical realizations of experimental vapor deposition protocols [9] have shown good success in creating well-annealed glasses [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The particle swaps enable a powerful tool to test ideas which have been previously inaccessible. Examples include demonstrated that surface mobility is indeed the mechanism for the deeply supercooled ultrastable glasses (see section 3.3) [208] and provide evidence in support of the non-equliibrium Gardner transition between glasses and jammed-like states [46,209]. Event-Chain Monte-Carlo An alternative route consists of implementing Monte-Carlo schemes that accelerate the equilibration through long-range coherent motions of the particles [198,199].…”
Section: Non-local Monte-carlo Techniquesmentioning
confidence: 99%
“…Some of these models can be equilibrated even beyond the timescales accessible in the laboratory. Thanks to this simulation approach, it becomes possible to scrutinize under experimentally relevant conditions several outstanding issues concerning glass formation, such as the entropy crisis [8], the kinetic stability of ultrastable glasses [9,10], jamming [11], and the Gardner transition [12][13][14]. These aspects are central in the current debate on the thermodynamic and dynamical properties of amorphous materials.…”
Section: Introductionmentioning
confidence: 99%